Konstruksi Buddhist Personality Scale Berdasarkan Tipologi Carita dengan Metode DeVellis - Setyoko, Rahmad (Kamaya: Jurnal Ilmu Agama, 2025)
This research aims to develop a personality scale based on the carita typology using the DeVellis method, test its validity and reliability, and interpret the results of measuring the Buddhist Personality Scale. This type of research is Research and Development with eight stages of DeVellis scale development. The test subjects were 86 Buddhists at the Mahabodhi Buddhist Center and the Tanah Putih Temple, Semarang. The validity of the scale was measured using Confirmatory Factor Analysis (CFA) and the reliability of the scale was measured using Cronbach's Alpha. This research produced a Buddhist Personality Scale which functions to measure personality type tendencies based on the Carita typology, namely: Ragacarita (Greedy), Dosacarita (Angry), Mohacarita (Dull), Saddhacarita (Faithful), Buddhicarita (Intelligent), and Vittakacarita (Speculative) . Scale construction is carried out in stages: 1) determining the measurement object based on theory; 2) assembling item based on the indicators; 3) selecting the scale format, namely the Likert Scale, 4) carrying out content validation by an expert panel; 5) revising items and adding accompanying items to produce 70 items; 6) carrying out validation tests with scale trials on research samples; 7) interpreting measurement results; and 8) scale optimization. The results of the validity test on the Buddha Personality Scale show that all items have a loading factor value > 0.500 so that the Buddha Personality Scale is appropriate to use to measure personality types. The Cronbach's Alpha value for each personality type instrument is > 0.800, so it can be stated that the Buddhist Personality Scale is very reliable as an instrument for measuring personality types based on the Carita typology. The results of the scale trial showed that 41 people had a tendency towards the Saddhacarita personality type, 28 people had a tendency towards the Buddhicarita type, and the rest had a tendency towards other personality types.